Weaving Activity and High Plasma Levels of Brain-Derived Neurothrophic Factor (BDNF) As A Protective Factors Against Cognitive Dysfunction in Middle-Aged Women - Yuniarni, Ruth Sharon; Widyadharma, I Putu Eka; Juhanna, Indira Vidiari; Rumai, I Made Winarsa; Dewi, Ni Nyoman Ayu; Komalasari, Ni Luh Gede Yoni (Riviera Publishing, 2025)
Cognitive dysfunction is a common problem associated with ageing and affects quality of life. As a repetitive activity, weaving and brain-derived neurotrophic factor (BDNF) levels are believed to be essential in maintaining cognitive function. This study aims to prove the relationship between weaving activity, BDNF levels, and cognitive dysfunction. This study is an observational study with a case-control design. The study subjects were middle-aged women (45–59 years) divided into two groups: CD (cases) and non-CD (controls). CD status was determined using the Mini-Mental State Examination (MMSE) score. Weaving activity was assessed through a questionnaire, with the criterion for active weaving being at least 3–5 times per week (minimum 60 minutes per session), categorised as weaving (+) and non-weaving (–). Plasma BDNF levels were measured using an ELISA kit and categorised as high BDNF (+) and low BDNF (–) based on the mean value. The researchers performed statistical analysis using the Chi-Square test and logistic regression. The Chi-Square test showed a significant association between weaving activity as a protective factor against CD occurrence (p < 0.001; OR: 0.038) and high BDNF levels as a protective factor against CD occurrence (p < 0.001; OR: 0.013). Multivariate analysis using logistic regression indicated that weaving activity (p = 0.001; AOR: 0.028; CI: 0.003–0.247) and high BDNF levels (p < 0.001; AOR: 0.011; CI: 0.001–0.100) were independent protective factors against CD occurrence. This study indicates that weaving activity and high plasma BDNF levels are independent protective factors against CD.